2005
DOI: 10.1007/s00253-005-0223-3
|View full text |Cite
|
Sign up to set email alerts
|

Microbial hydroxylation of imidacloprid for the synthesis of highly insecticidal olefin imidacloprid

Abstract: Microorganisms that bring about the aerobic transformation of imidacloprid (IMI) were isolated and screened, and the microbial regio- and stereoselective hydroxylation of IMI was studied. Some bacteria and fungi transformed IMI to 5-hydroxyl IMI. Bacterium Stenotrophomonas maltophilia CGMCC 1.1788 resting cells transformed IMI into R-5-hydroxyl IMI at the highest conversion rate. The enzyme catalyzed the stereoselective hydroxylation at position C12 of IMI in the imidazolidine ring. Under acidic conditions, 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 20 publications
2
66
0
Order By: Relevance
“…Previously we reported that some strains of bacterium Stenotrophomonas maltophilia isolated from soils and screened from stock culture were able to hydroxylate IMI to form 5-hydroxy IMI that was easily converted to olefin IMI under acid condition. The insecticidal activity of olefin IMI was 19 times higher than that of IMI against horsebean aphid (Dai et al 2006). These results lead a new investigation on the microbial transformation to understand why longer time and better control are achieved when IMI is applied as a soil drench application than the other methods.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Previously we reported that some strains of bacterium Stenotrophomonas maltophilia isolated from soils and screened from stock culture were able to hydroxylate IMI to form 5-hydroxy IMI that was easily converted to olefin IMI under acid condition. The insecticidal activity of olefin IMI was 19 times higher than that of IMI against horsebean aphid (Dai et al 2006). These results lead a new investigation on the microbial transformation to understand why longer time and better control are achieved when IMI is applied as a soil drench application than the other methods.…”
Section: Introductionmentioning
confidence: 86%
“…Large-scale preparation of metabolites of AAP The biotransformation process of AAP in a 5-L fermenter was described in a previous study (Dai et al 2006). In the end of the transformation, cells were removed by centrifugation at 6,000g for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…Many researchers have also reported degradation of organic pollutants at alkaline conditions. However, it is slow and also reflected through our results [24,27,28].…”
Section: Discussionmentioning
confidence: 52%
“…The 5-hydroxy IMI and olefin IMI were synthesized as reported by Dai et al 5) Acetonitrile and acetic acid (High Performance Liquid Chromatography (HPLC) grade) were purchased from TEDIA Company, USA. Other analytic reagents were purchased from Bio Basic Inc.…”
Section: Chemicalsmentioning
confidence: 99%
“…4) Our data also shows that Stenotrophomonas maltophilia can transform IMI to 5-hydroxy IMI, which can be further transformed to olefin IMI under chemical conditions. 5) More recently, we found that when succinate was used as an utilizable substrate, S. maltophilia CGMCC 1.1788 cometabolized IMI directly to olefin IMI via 5-hydroxy IMI.…”
Section: Introductionmentioning
confidence: 99%